2019
DOI: 10.1051/0004-6361/201935340
|View full text |Cite
|
Sign up to set email alerts
|

VLA cm-wave survey of young stellar objects in the Oph A cluster: constraining extreme UV- and X-ray-driven disk photoevaporation

Abstract: Observations of young stellar objects (YSOs) in centimeter bands can probe the continuum emission from growing dust grains, ionized winds, and magnetospheric activity, which are intimately connected to the evolution of protoplanetary disks and the formation of planets. We have carried out sensitive continuum observations toward the Ophiuchus A star-forming region using the Karl G. Jansky Very Large Array (VLA) at 10 GHz over a field-of-view of 6 with a spatial resolution of θ maj × θ min ∼ 0 . 4 × 0 . 2. We ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…The resulting on-sky surface brightness distribution is shown in Figure 2, and results in a total disc integrated flux density of 0.15 mJy, which is comparable to the free-free corrected measurements of dust continuum emission from young discs at similar frequencies (e.g. HL Tau, Carrasco-González et al 2019; the ρ Oph A members, Coutens et al 2019).…”
Section: Radiative Transfer Calculationssupporting
confidence: 69%
See 1 more Smart Citation
“…The resulting on-sky surface brightness distribution is shown in Figure 2, and results in a total disc integrated flux density of 0.15 mJy, which is comparable to the free-free corrected measurements of dust continuum emission from young discs at similar frequencies (e.g. HL Tau, Carrasco-González et al 2019; the ρ Oph A members, Coutens et al 2019).…”
Section: Radiative Transfer Calculationssupporting
confidence: 69%
“…In addition, the extremely large collecting area of SKA1 will result in sensitivities that are a factor of 3-4 higher than those currently available with the JVLA dishes. Several works have examined the potential that the SKA has in providing significant contributions in our understanding of star and planet formation (Hoare et al 2015;Testi et al 2015), and pathfinder studies using the JVLA have started to determine optimal targets for first observations (Coutens et al 2019). However, there are currently no detailed investigations on the potential for the SKA to characterise the cm-dust component of planet forming discs.…”
Section: Introductionmentioning
confidence: 99%
“…also found a smaller strongly collimated outflow associated this component. Interestingly, VLA 1623 B was determined to be variable at centimeter wavelengths byCoutens et al (2019).…”
mentioning
confidence: 99%
“…Santangelo et al (2015) also found a smaller strongly collimated outflow associated this component. Interestingly, VLA 1623 B was determined to be variable at centimeter wavelengths by Coutens et al (2019). The submillimeter light curve for secular source Orion NGC 2068, V1647 Ori is presented in Figure B.7.…”
Section: B5 Serpens Main Smm 10: Curved Groupmentioning
confidence: 99%